Arginine vasopressin antagonism in heart failure: Current status and possible new directions. Issue 1 (July 2019) - Goldsmith, Steven R.
Highlights: Arginine vasopressin (AVP) levels are increased in heart failure (HF) aeceptors. V1a receptor antagonism could mitigate long-term left ventricular remodeling since its intracelluar signaling is similar to angiotensin II. V2 antagonism produces free water diuresisa and when added to diuretics enhances decongestion without adverse renal or neurohormonal effects. Outcomes in acute HF remain poor.The use of a V2 or combined V1a/V2 antagonist could prove to be an effective but safer therapy than loop diuretics in acute HF. Abstract: Modulating neurohormonal imbalance is the cornerstone of successful therapy in patients with chronic heart failure with reduced ejection fraction (HFrEF). Plasma arginine vasopressin (AVP) levels are elevated in HFrEF and may contribute to disease progression by excess signaling at either the V1a or V2 receptors. The effects of V1a receptor antagonism are almost completely unexplored, but V1a signaling is closely related to that for angiotensin II and blocking that receptor deserves further study. Interfering with V2 signaling causes free water diuresis and improves congestion without worsening renal function when added to loop diuretics but alone did not improve outcomes when carried into the post-acute phase in one large study. Outcomes in chronic HFrEF are quite good while outcomes in acute HF remain poor. Therefore, further study of V2 or combined V1/V2 blockade of the effects of AVP would most likely yield positive results in patients with acute HF, perhaps especially as alternative, not adjunctive therapy to loop diuretics.